2016
DOI: 10.1038/srep22844
|View full text |Cite
|
Sign up to set email alerts
|

Immune Infertility Should Be Positively Diagnosed Using an Accurate Method by Monitoring the Level of Anti-ACTL7a Antibody

Abstract: Infertility is currently a major public health problem. Anti-sperm antibodies (ASAs) markedly reduce sperm quality, which can subsequently lead to male and/or female infertility. The accurate detection of ASAs derived from specific spermatozoa is, therefore, clinically useful. We have focused on the spermatozoa-specific expression protein ACTL7a for many years and have developed an enzyme-linked immunosorbent assay (ELISA) to detect the concentration of anti-ACTL7a antibodies in fertile sera (n = 267) and infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…On the other hand, Fu et al 22 recently developed an enzyme‐linked immunosorbent assay (ELISA) using anti‐actin‐like protein (ACTL)7a antibodies because they thought that previously available tests of ASA detection showed only the binding of antibodies on the sperm surface, but no antigenic information could be applied 23‐25 . They have focused on the sperm‐specific expression protein ACTL7a and found that ACTL7a could be recognized by the antibodies contained in infertile serum, which could reduce mouse fertility rates to zero 26 .…”
Section: Detection Of Anti‐sperm Antibodiesmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, Fu et al 22 recently developed an enzyme‐linked immunosorbent assay (ELISA) using anti‐actin‐like protein (ACTL)7a antibodies because they thought that previously available tests of ASA detection showed only the binding of antibodies on the sperm surface, but no antigenic information could be applied 23‐25 . They have focused on the sperm‐specific expression protein ACTL7a and found that ACTL7a could be recognized by the antibodies contained in infertile serum, which could reduce mouse fertility rates to zero 26 .…”
Section: Detection Of Anti‐sperm Antibodiesmentioning
confidence: 98%
“…If they set the standard at a strongly positive value, calculated by ROC curve, the positive predictive value of the antibody detection reached 100 percent, with a false‐positive rate of zero. They concluded that the ELISA method developed for anti‐ACTL7a antibody detection is therefore sensitive, accurate, and easy to perform, making it an excellent potential tool for future clinical use 22 …”
Section: Detection Of Anti‐sperm Antibodiesmentioning
confidence: 99%
“…The spontaneous pregnancy rates in these two groups followed the same pattern, being 20% in the ASAnegative controls and 6.5 % in the ASA-positive patients. 114 Additional new, sensitive technologies for monitoring the presence of ASA in semen and blood 116,117 that target specific antigens 118,119 may provide this field with the additional stimulus it needs to become a valid component of our diagnostic armamentarium.…”
Section: Autoimmunity Inflammation and Infectionmentioning
confidence: 99%
“…However, this production-related issue is studied insufficiently. There are numerous violations in the animal management and feeding, their technological exploitation and artificial fertilization which leads to suppression of the reproductive cycle in sows due to alimentary and symptomatic infertility, fertilization disruptions due to an increased sperm antibody titer, which is characteristic of the immune infertility [1,2].…”
Section: Introductionmentioning
confidence: 99%